Pengaruh Ion Hg(II) Terhadap Efektivitas Fotoreduksi Ion Cu(II) Terkatalisis TiO2 dalam Limbah Cair Industri Kerajinan Perak di Desa Ungga Kec. Praya Lombok Tengah - Hatimah, Husnul (IKIP Mataram, 2018)
In this study a study of the effect of TiO2 photocatalysts and Hg (II) ions in thewastewater of the silver industry in Ungga Village, Kec. PrayaKab. CentralLombok to the effectiveness of Cu (II) photoreduction which is catalyzed byTiO2. The photoreduction process is carried out by irradiating liquid wastecontaining Cu (II) and Hg (II) ions without or by adding TiO2 photocatalystpowder in a closed reactor equipped with UV light. The condition of thephotoreduction process is 50 mL of silver waste containing Cu (II) and Hg (II)with a reaction time of 24 hours and a mass of TiO2 20 mg at 10 ppm Cu (II) ionconcentration. Photoreduction results are determined based on the difference inthe concentration of Cu (II) ions with the concentration of residual Cu (II) ionsin silver waste without the addition of TiO2 photocatalysts. Furthermore, thedata obtained compared to the results of Cu (II) photoreduction catalyzed bypure TiO2 laboratory scale. The amount of metal in the mixture was determinedby the Atomic Absorption Spectrophotometry (AAS) method. The results showedthat in silver handicrafts containing Cu (II) and Hg (II) ions the addition of TiO2can increase the effectiveness of Cu (II) photoreduction from 6.57% to 33.38%,which begins with the adsorption process. Hg (II) in silver handicraft wastecauses inter-metal reduction competition so that it can reduce the effectiveness ofCu (II) ion photoreduction catalyzed by TiO2 by 9.84% when compared to thepercentage of Cu (II) ion Ti2O scale scale laboratory testing.